Penggunaan Kulit Lai (Durio kutejensis (Hassk) Becc.) Sebagai Bioadsorben Untuk Menurunkan Kadar Amonia Pada Limbah Cair Domestik Rumah Sakit - Sitanggang, Yusril Bahri; Nia Febrianti; Ariani, Ismi Khairunnissa (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2025)
Hospital domestic wastewater comes from the operating room, laundry, bathroom, kitchen and laboratory equipment washing room. The ammonia level in one of the hospitals in Balikpapan is 27.1 mg/L which exceeds the quality standard of 10 mg/L. The high concentration of ammonia can cause eutrophication in water bodies. Therefore, appropriate treatment of hospital wastewater is needed to prevent damage to aquatic ecosystems. The adsorption method is an alternative treatment method in hospital domestic wastewater to set aside ammonia parameters, because the tools applied are simple so that implementation is easy to apply, and the adsorbent materials used are easily available, and also the costs used are cheap and do not require large areas of land. The bioadsorbent used is lai peel and activated with sodium carbonate (Na2CO3). Variations in the dose of lai peel bioadsorbent and contact time had a significant effect on ammonia removal efficiency. The optimum condition occurred at a dose of 1 gram/100mL and a contact time of 50 minutes with an optimum removal efficiency of 73%. Adsorption capacity to the dose of lai peel bioadsorbent has no significant effect while adsorption capacity to contact time has a significant effect. The optimum condition of adsorption capacity occurred at a dose of 0.4 grams/100mL and a contact time of 50 minutes with an adsorption capacity of 2.69 mg/g.